Energy education: adapting to learning preferences and pedagogical strategies - Majid, Nik Aida Mastura Nik Abdul; Osman, Kamisah; Yee, Tan Siok (Intelektual Pustaka Media Utama, 2025)
Addressing diverse learning needs in energy education is vital for fostering environmental awareness and sustainability. This study aims to identify students’ learning preferences, the challenges teachers encounter when teaching energy-related topics, and the most effective pedagogical strategies to address these challenges. Using a mixed-methods approach, quantitative surveys were administered to 163 15-year-old students in Bintulu, Sarawak, to assess learning preferences, demographic characteristics, and the difficulty level of various science topics, complemented by qualitative semi-structured interviews with three experienced science teachers. Quantitative data were analyzed using descriptive statistics to reveal trends and patterns, while thematic analysis of interview data provided deeper insights into teaching challenges. The study found “energy and sustainable life” to be the most challenging theme while teachers highlighted four major obstacles: i) abstract concepts; ii) weak mathematical skills; iii) terminology confusion; and iv) resource constraints. Effective strategies identified include incorporating digital learning tools, interactive and real-world applications, and enhanced teacher support. These findings underscore the need for tailored instructional approaches that leverage technology and address diverse learning preferences to improve student engagement and comprehension in energy-related topics. Future research should focus on developing innovative teaching methods and evaluating their long-term impacts on student learning and environmental consciousness.